The missing piece : radiological and surgical management of a body packer with a methamphetamine packet stuck in the stomach - Abdul Rashid, Saiful Nizam; Mohamad Saini, Suraini; Ab. Hamid, Suzana; Fakhrizzaki, Ahmad Afkar; Bahari, Norafida (Elsevier, 2013)
Introduction Usually, body packers have no complications and current recommendations for such patients advise a conservative approach, waiting for a spontaneous packet’s evacuation with the bowel movement. In case of complications such a packet stuck in the stomach, a surgical approach seems to be safer than an endoscopic approach.